Proximate, Minerals and Fatty Acids Compositions in Different Muscles of Wild and Cultured Osteobrama belangeri (Valenciennes, 1844) - Devi, Ngangom Lucky; Sarojnalini, Chungkham (Asian Journal of Biological and Life Sciences)
Osteobrama belangeri is a medium carp that belongs to the family cyprinidae. Once abundantly found in Myanmar and India, the population of this fish in the wild especially in India has depleted significantly in the last four decades and has been declared “Near threatened” in the recent past. This article aims to quantify and compare the proximate composition, minerals and fatty acids in wild and cultured Osteobrama belangeri. Fatty acids are analyzed using Gas Chromatography- Mass Spectrometry (GC-MS). Minerals analysis was carried out using Inductively Coupled Plasma- Optical Emission Spectroscopy (ICP-OES). Elements like Na, K, Fe, Cu, Zn and Se are found higher in the wild fish whereas Ca, Mg and Mn are found higher in the cultured fish. Palmitic acid, oleic acid and linoleic acid are the main fatty acids found in all the samples. The wild fish contains a relatively higher level of ω-3 and ω-6 polyunsaturated fatty acids, particularly docosahexaenoic acid, linoleic acid and arachidonic acid. The results also reflect a low total ω-3:ω-6 ratio in both wild and cultured fishes indicating a beneficial aspect for consumption. The results show that both cultured and wild species contain significant and comparable levels of valuable nutrients such as minerals (Na, K, Fe, Cu, Zn, Se Ca, Mg and Mn) and fatty acids especially oleic acid, linoleic acid, arachidonic acid and docosahexaenoic acid. Since the fish remains popular in India, it is suggested that the cultured fish be utilized for consumption while the wild fish be preserved.
Keywords: Fatty acids; Minerals analysis; Osteobrama belangeri; Proximate Composition